INDIGENOUS METHODS OF EDUCATION AS PRACTISED BY THE KIPSIGIS - Bii, Sammy kipkorir (Machakos University, 2019)
This paper presents an overview of indigenous methods of education used by the kipsigis and its Relevance to modern education. The article is descriptive and relied heavily on published works. It shows that kipsigis instructed children through formal and informal methods. Informal methods of instructions included involving children in productive work and observation. The boys were engaged in looking after livestock while girls looked after younger brothers and sisters. Children also learnt how to observe. They also learned through play. Other forms of informal methods were myths, legends folklores, riddles and songs. Myths are regarded as tales imaginatively describing or accounting for natural phenomena. The kipsigis had songs for various occasions .Besides the numerous folksongs with which children were associated with as they grew up, there existed rich children’s oral literature. Folktales among kipsgis were based on day to day happenings. Asking of riddles was a very special form of amusement. Some riddles seemed to be simple while others were complex. Proverbs were used wisely in ordinary conversation. Formal methods of instructions were initiation and apprenticeship. The period of circumcision was the most important time in the life of the kipsigis. It marked the passage from childhood to adulthood. Medicine was widely practiced in kipsigis pre-colonial times. When children were sick or ill, the mother was responsible for giving advice and first aid before the father’s assistance was resorted to. Men and women learned this skill from their parents. There were individuals who were recognized as better herbalists. A person who wanted his child to learn the skills from a specialist would pay a fee and training took a period of time .The skill of iron work was transmitted from father to son .Weaving was done by women and was taught to girls .The art of pottery was learnt by the kipsigis women from luo and Abagusii.The paper concludes that there were two methods of instructions used by the kipsigis to teach their children in pre-colonial times; these were formal and informal methods.
Keywords: Informal methods; Formal methods; Myths; Legends; Riddles; Proverbs